PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB GOOGLE SITES MENGGUNAKAN PENDEKATAN STREAM (SCIENCE, TECHNOLOGY, RELIGION, ENGINEERING, ART, AND MATHEMATICS) PADA MATERI KIMIA HIJAU - Defri Hadi Hidayat; Heppy Okmarisa; Ardiansyah Ardiansyah; Neti Afrianis (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2025)
Developing Web Google sites based learning medium with STREAM (Science, Technology, Religion, Engineering, Art, and Mathematics) approach on Green Chemistry lesson was conducted. This research was instigated by the lack of Technologycal based learning media innovation in learning chemistry. This research aimed at finding out the design of Web Google sites based learning medium with STREAM approach on Green Chemistry lesson and finding out media validity, material validity, teacher practicality, and student response to Web Google sites based learning medium with STREAM approach on Green Chemistry lesson.  Research and Development (R&D) method was used in this research with Design, Development, Research (DDR) model with the following steps: analysis, design, development, and evaluation.  This research was conducted at State Senior High School 8 Pekanbaru.  The instruments of collecting data were interview sheet, validity test questionnaire, practicality test questionnaire, and student response questionnaire.  The result percentages of validity test were 95% by material experts and 95% by media experts with very valid criteria.  The percentage of teacher practicality test was 90% with very practical criteria, and the percentage of student response test was 94.04% with very interesting criteria.  So, it could be concluded that Web Google sites based learning medium with STREAM approach on Green Chemistry lesson was very appropriate to be used in the learning activity.